2021
DOI: 10.3390/genes12091386
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Polymorphism of TSLP/TSLP Receptors as Potential Diagnostic Markers of Colorectal Cancer Progression

Abstract: Colorectal cancer (CRC) is the third most common malignancy and the fourth leading cause of cancer-related mortality worldwide. Inflammation is considered as a critical driver for CRC development and growth. We investigated the association between polymorphisms/expression levels of thymic stromal lymphopoietin (TSLP) /TSLP receptors and CRC risk in Saudi population. DNA samples were isolated from blood samples from 220 participants. Case subjects were 112 patients diagnosed with CRC, while control subjects wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Increased expression of TSLP and TSLPR has also been reported in colorectal cancer, and the TSLP SNP rs10043985 was shown to be a biomarker for an increased risk of colorectal cancer in the Saudi population 151 . Nevertheless, antitumour effects of TSLP in colorectal cancer have also been reported 152 , with decreased TSLP levels in tumour than in adjacent tissue and TSLP levels negatively correlated with the clinical staging score.…”
Section: Tslp and Cancermentioning
confidence: 97%
“…Increased expression of TSLP and TSLPR has also been reported in colorectal cancer, and the TSLP SNP rs10043985 was shown to be a biomarker for an increased risk of colorectal cancer in the Saudi population 151 . Nevertheless, antitumour effects of TSLP in colorectal cancer have also been reported 152 , with decreased TSLP levels in tumour than in adjacent tissue and TSLP levels negatively correlated with the clinical staging score.…”
Section: Tslp and Cancermentioning
confidence: 97%
“… 15 Semlali et al evaluated the TSLP rs10043985 and IL-7R rs1053496 SNPs and found that they could be used as markers for CRC development in the Saudi population, based on a case–control study. 16 In addition, Li et al found that the ADCY9 polymorphism, rs2230742, was related to an increased risk of CRC in the Chinese Han population. 17 Moreover, the rs12674822 variant of ANGPT2 was reported to be associated with CRC risk in Chinese subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Each SNP was located either in promoter, intron, or exon regions (Tables S1 and S2), which may lead to a change in the regulation of the protein or modification in protein folding or function. As described by our previous works [23][24][25][26], a total of 8 µL of the final reaction mix and 2 µL of DNA (10 ng/µL) were distributed in an optical reaction plate. The SNP reaction mix contained 5.3 µL of TaqMan ® genotyping master mix (Applied Biosystems, Foster City, CA, USA), 2.5 µL of nuclease-free water, and 0.2 µL of SNP.…”
Section: Snp Selection Taq Man Genotyping Assaymentioning
confidence: 99%